TESTING THE WEAK-FORM MARKET EFFICIENCY OF THE CYPRUS STOCK EXCHANGE (CSE) - Kyriacou, John (2008)
The primary objective of this study is to test whether the Cyprus Stock Exchange (CSE) is atleast weak form efficient. Tests of randomness and tests of predictability via the use of technical analysis will be the fundamental approaches for the investigation purposes. The test of autocorrelations, the run test, and the Lo and MacKinlayÃÂ¢ÃÂÃÂs variance ratio test are applied on the series of daily returns of the CSE General Index and the Cyprus FTSE index to test for the first condition of weak-form market efficiency. The results derived prove that the CSE is inconsistent with random walk theory. Technical analysis techniques reveal that the Cyprus market is predictable and sophisticated investors can exploit the market inefficiencies. The implication of this scenario is that the CSE is not weak form efficient.